Soft and plasmonic hydrogel optical probe for glucose monitoring - Guo Jingjing; Zhou Bingqian; Du Zhou; Yang Changxi; Kong Lingjie; Xu Lijun (Nanophotonics, 2021)
Glucose monitoring sensors with high softness and flexibility are critical for the developments of wearable and implantable healthcare devices that enable diagnosis, prognosis, and management of diabetes. The design and implementation of such sensors have been extensively exploited by electrochemical strategies, which, however, suffer from poor reusability and complex modification procedures, and necessitate frequent calibration or sensor replacement due to enzymatic reaction instability. Here, a soft and plasmonic hydrogel optical sensor is created for quantitative and continuous glucose monitoring under physiological conditions. The optical sensor consists of a flexible optical fiber made from composites of gold nanoparticles and glucose-responsive hydrogels. The reversible binding of glucose to the nanocomposite optical fiber results in dynamic volume expansion of the hydrogel matrix, which modulates the localized surface plasmon resonance effect, enabling glucose to be quantified from the light transmission. To achieve robust readout, a dual-wavelength differential approach is employed to endow the sensor with self calibration capability. We show that the sensor is reversible and reusable for detecting physiological glucose levels with high linearity and negligible hysteresis. The soft and flexible glucose sensor holds great promises of serving as a minimally-invasive probe for point-of-care glucose monitoring in clinics.